O adiamento dos Jogos Olímpicos e Paralímpicos de Tóquio 2020 foi uma decisão correta? - de Carvalho Guerreiro, R.; Silva, A.; de Araújo Andrade, H.; Grade Biasibetti, I.; Vital, R.; Gley Vital da Silva, H.; Rodrigues da Silva, F.; de Mello, M. T. (Revista Brasileira de Medicina do Esporte, 2020)
In December 2019, Wuhan, in China, attracted international attention due to a pneumonia outbreak caused by the new coronavirus (2019-nCoV). Infection by 2019-nCoV is more likely in elderly people with comorbidities or with associated chronic diseases. Due to the high transmission rate among humans, this disease is rapidly disseminated, which led to several events being canceled, including the Tokyo 2020 Olympic and Paralympic Games. The aim of this article is to discuss the risk factors for Olympic and Paralympic athletes, as well as for spectators, that justify the decision to postpone the Tokyo Games 2020. Regular physical exercise is associated with health and the prevention of chronic diseases. Although athletes generally appear to be healthy and physically fit, this may not be true. The immune system, which protects the organism from invasive microorganisms, can be affected by the duration and quality of sleep, as well as by physical exercise which influences the quality of the immune response. High volumes of high-intensity physical exercise, as well as changes in sleep patterns during the pre-competition period and the impacts of jet lag on athletes traveling for the Tokyo Games in 2020 may lead to immune system suppression, making these groups more vulnerable to infection by 2019-nCoV. Moreover, during the period planned for the games in 2020 the pandemic may be subsiding in some countries and increasing in others, and this was also taken into consideration as a risk factor. Hence, the decision taken to postpone the Tokyo 2020 Olympic and Paralympic Games until 2021 due to the 2019-nCoV was the correct one, and was extremely important to protect the health of Olympic and Paralympic athletes, as well as spectators.